"Environmental capabilities, proactive environmental strategy and competitive advantage: A natural-resource-based view of firms operating in India". (1st April 2021) - Mishra, Poornima; Yadav, Manmohan
Abstract: Drawing on the natural resource-based theory, the study examines the relationship of specific environmental capabilities, proactive environmental strategy (PES), and competitive advantage. In addition, it explores how perceived uncertainty and hostility in the general business environment moderate the deployment of strategic proactivity capability in formulating proactive environmental strategy. Accordingly, hypotheses were formulated, which were then tested using multiple hierarchical regression and bootstrapping mediation analysis on the survey data collected from 162 firms operating in India. The results indicate that the capabilities of shared vision, strategic proactivity, and continuous innovation are pre-requisites to formulate a PES. Furthermore, the findings confirm that PES mediates the relationship between environmental capabilities and competitive advantage. Moderation results reveal that perceived uncertainty positively moderates the relationship between strategic proactivity and a PES. However, the moderating impact of perceived hostility was found to be insignificant. The study contributes to the understanding of natural-resource-based view and contingent influence of external variables in designing PES by firms in the Indian business context. These findings provide important managerial implications for the deployment of environmental capabilities to pursue PES in gaining a competitive advantage.